The Rise and Development of Hunan Gong Bi Painting from 1980 to 2000 : Expressing Life Through Tradition - Kang, Xiao; Wan Jamarul Imran, Wan Abdullah Thani (ADWEN HOUSE PUBLISHING LIMITED GROUP LIMITED, 2024)
Gong Bi painting, one of China's most influential traditional art forms, evolved significantly in the 20th century, transforming into modern Gong Bi painting. Hunan Gong Bi Painting (HGP) experienced a resurgence in the 1980s, becoming a prominent force in the field. This resurgence introduced a new style, "using tradition to express contemporary life," which blended classical techniques with modern themes. During this period, Hunan Gong Bi painting achieved significant accomplishments, becoming a major influence in the national Gong Bi painting scene. This paper aims to analyze the specific characteristics of "using tradition to express contemporary life" from an iconographic perspective. The study employs qualitative research methods, including case studies, observation, interviews, literature analysis, and thematic analysis. Findings reveal that HGP retained the intricate line work and refined color application typical of traditional Gong Bi painting. In terms of theme, Hunan Gong Bi painting focused more on contemporary life and natural scenery. This fresh style met the post-Cultural Revolution society's need for diverse cultural forms and artistic styles.